2017
DOI: 10.1186/s13550-017-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of oxygen metabolism in the intratumoral hypoxia: 18F-fluoromisonidazole and 15O-labelled gases inhalation PET

Abstract: BackgroundIntratumoral hypoxia is one of the resistant factors in radiotherapy and chemotherapy for cancer. Although it is detected by 18F-fluoromisonidazole (FMISO) PET, the relationship between intratumoral hypoxia and oxygen metabolism has not been studied. The purpose of this study was to evaluate the intratumoral perfusion and oxygen metabolism in hypoxic regions using the rat xenograft model. Ten male Fischer rats with C6 glioma (body weight = 220 ± 15 g) were investigated with 18F-FMISO PET and steady-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Theoretically, 16:1 might be expected by biochemistry in anoxic tissue. The discrepancy can be explained by 1) limited spatial resolution of PET showing a mixture of hypoxic and non-hypoxic cells, not anoxic (only hypoxic, FMISO starts accumulation below an oxygen level of 10 mmHg), 2) hypoxia may reduce metabolism and increase oxygen extraction fraction [29], 3) in hypoxic area, necrosis is developing and cell density is decreasing, FDG uptake may be decreased, 4) FDG uptake does not completely reflect the entire process of glycolysis, but rather reflects glucose transporters and the hexokinase activity only [30].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, 16:1 might be expected by biochemistry in anoxic tissue. The discrepancy can be explained by 1) limited spatial resolution of PET showing a mixture of hypoxic and non-hypoxic cells, not anoxic (only hypoxic, FMISO starts accumulation below an oxygen level of 10 mmHg), 2) hypoxia may reduce metabolism and increase oxygen extraction fraction [29], 3) in hypoxic area, necrosis is developing and cell density is decreasing, FDG uptake may be decreased, 4) FDG uptake does not completely reflect the entire process of glycolysis, but rather reflects glucose transporters and the hexokinase activity only [30].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported about the intratumoral heterogeneity with hypoxic and necrotic regions in the C6 glioma xenograft by comparing 18 F-FMISO and 15 O-labeled gas PET to histological analysis [ 11 ]. Another previous study reported the characteristic difference in the tumor xenograft by comparing three tumor cell lines [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FMISO was prepared using the same method as previously mentioned ( 16 ). 18 F-HF was produced by an in-house cyclotron (HM-12S; Sumitomo Heavy Industry) and 18 F-FMISO was prepared with a UG-M1 synthesizer module using 3-(2-nitroimidazo-1-yl)-2-Otetrahydropyranyl-1-O-toluenesulfonyl-propanediol as a labeling precursor.…”
Section: Methodsmentioning
confidence: 99%
“…18 F-HF was produced by an in-house cyclotron (HM-12S; Sumitomo Heavy Industry) and 18 F-FMISO was prepared with a UG-M1 synthesizer module using 3-(2-nitroimidazo-1-yl)-2-Otetrahydropyranyl-1-O-toluenesulfonyl-propanediol as a labeling precursor. 18 F-FMISO PET-CT was subsequently performed ( 16 , 17 ).…”
Section: Methodsmentioning
confidence: 99%